2022
DOI: 10.1111/cogs.13139
|View full text |Cite
|
Sign up to set email alerts
|

A SPoARC of Music: Musicians Spatialize Melodies but not All‐Comers

Abstract: Recent studies on the spatial positional associated response codes (SPoARC) effect have shown that when Western adults are asked to keep in mind sequences of verbal items, they mentally spatialize them along the horizontal axis, with the initial items being associated with the left and the last items being associated with the right. The origin of this mental line is still debated, but it has been theorized that it necessitates specific spatial cognitive structures to emerge, which are built through expertise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…This result was obtained using the t-test family of tests, a Type I error of α = .05, a two-sided criterion for detection of a significance, a power of 80%, and an effect size (Cohen's d) superior to .50. Note that this type of effect size is usually reported when a power analysis is done in the domain; e.g., Hartmann et al (2021) reported a Cohen's d = .51 and a Cohen's d = .65; Guida and Porret (2022), reported Cohen's d = .51. A second power analysis showed that a sample of 95 participants was required to reach a power of 80% when running a correlational analysis based on α = .05 and Cohen's d = .28 (as reported by van Dijck et al, 2022, in their correlational analysis).…”
Section: Participantsmentioning
confidence: 99%
“…This result was obtained using the t-test family of tests, a Type I error of α = .05, a two-sided criterion for detection of a significance, a power of 80%, and an effect size (Cohen's d) superior to .50. Note that this type of effect size is usually reported when a power analysis is done in the domain; e.g., Hartmann et al (2021) reported a Cohen's d = .51 and a Cohen's d = .65; Guida and Porret (2022), reported Cohen's d = .51. A second power analysis showed that a sample of 95 participants was required to reach a power of 80% when running a correlational analysis based on α = .05 and Cohen's d = .28 (as reported by van Dijck et al, 2022, in their correlational analysis).…”
Section: Participantsmentioning
confidence: 99%